Novel Targets in a High-Altitude Pulmonary Hypertension Rat Model Based on RNA-seq and Proteomics - Xu, Xiang; Li, Hanlu; Wei, Qingxia; Li, Xin; Shen, Yanying; Guo, Ge; Chen, Yibing; He, Kunlun; Liu, Chunlei (Frontiers in Medicine, 2021)
High-altitude pulmonary hypertension (HAPH) is a complication arising from an inability to acclimatize to high altitude and is associated with high morbidity and mortality. We aimed to analyze the effects of macitentan, selexipag, riociguat, and reoxygenation on HAPH, and to screen possible targets of these treatments for future drug screening. Rats were subjected to hypobaric hypoxia for 35 d to induce HAPH, and treated with vehicle or selexipag, macitentan, riociguat, or with reoxygenation, from day 21 to 35. Selexipag, macitentan, and reoxygenation prevented an increase in mean pulmonary artery pressure and hypoxia-induced right ventricular hypertrophy, compared to the vehicle. Riociguat had little effect. RNA-seq and proteomics revealed strong correlations between responses to the three drugs, which had almost identical effects. GO-enrichment revealed that the differentially expressed genes included those involved in metabolic regulation, transcription, and translation. Various molecular pathways were annotated. Selexipag, macitentan, and reoxygenation ameliorated HAPH. Serpina1, Cryz, and Cmc1 were identified, via multi-omics screening, as key genes involved in HAPH. These findings provide new insights into the targeted drug mechanisms in HAPH.